Study the basic infrared tx-rx circuit design for robot - Nik Ahmad Faiz Abdul Jamel
This final year project is about to study, construct and test a simple circuit of Infrared Transmitter and Infrared Receiver. Another objective is to apply and show that the circuit is can be used in any robot as a transmitter and receiver signal application to avoid hitting obstacle in the route.